266 Mini C-Arm Use in The Emergency Department for Fracture Management During The COVID-19 Pandemic: A Pilot Study in A Tertiary Paediatric Referral Centre. (4th May 2021) - Rammohun, A; Studnicka, K; Talbot, C
Abstract: Introduction: We introduced the use of a Mini C-arm in managing distal limb fractures to minimise admissions and patient flow within the hospital. Method: Prospective data collected between April and June 2020. Treatment details and imaging obtained from patient notes and PACS. A matching group from 2019 analysed for comparison. Results: Mini c-arm was used for manipulation of closed fractures of forearm (9), tibia (2), distal humerus (1), and foreign body removal (1). 11 procedures performed in ED with intranasal diamorphine and Entonox (5), intravenous Ketamine (5), or local anaesthetic (1), two in fracture clinic under Entonox. Fracture position was on average 7° from the anatomical. 1 Distal humerus required surgical correction. 1 admission after sedation. In the control group, 8 patients underwent manipulation under GA (4 ORIFs) and 2 procedures were done under sedation in ED. All patients were admitted. The quality of reduction varied on average 4º from anatomical. No patients required repeated procedures and all were followed up in a face to the face fracture clinic. Conclusions: Reduced admission rate, need for GA and flow to RD without an obvious reduction in the quality of manipulation resulted from both mini c-arm use and good cooperation with ED facilitating the sedation.